Development features of the small and medium businesses in the Republic of Kazakhstan - Usenbaev, T.M.; Alina, G.B.; Jumabekova, A.T.; Toizhigitova, Z.A.; Yessengeldinova, S.Z. (BUKETOV BUSINESS REVIEW, 2019)
Small and medium-sized business is one of the main drivers of social and economic development of modern society. Its development contributes to the formation of market relations and the formation of the middle class. The inherent flexibility, mobility and adaptability of small and medium-sized businesses to volatile market conditions can solve problems of social stability, employment and saturation of the consumer market. The authors of the article reviewed the peculiarities of the development of small and medium-sized businesses in the Republic of Kazakhstan. A detailed analysis of business activities on the scale of the national economy and in terms of regions has been carried out. Special attention is paid to the role of credit institutions in the further formation of small and medium-sized businesses in the state. The scientific article explores in detail the reasons for the decline in the contribution of small and medium-sized businesses to the economy, insufficient financing, problems faced by second-tier banks in lending this type of business activity. In order to modernize Kazakhstan 's economy and move it to an innovative development path, it is impossible without the active participation of small and medium-sized enterprises. The authors of the article made recommendations for the effective development of small and medium-sized businesses in the Republic of Kazakhstan in the conditions of the modern economy, its stable development in the long term.